Future Directions for Chemosensory Connectomes: Best Practices and Specific Challenges - Veldhuizen, Maria G.; Cecchetto, Cinzia; Fjaeldstad, Alexander W.; Farruggia, Michael C.; Hartig, Renée; Nakamura, Yuko; Pellegrino, Robert; Yeung, Andy W. K.; Fischmeister, Florian Ph. S. (Frontiers in Systems Neuroscience, 2022)
Ecological chemosensory stimuli almost always evoke responses in more than one sensory system. Moreover, any sensory processing takes place along a hierarchy of brain regions. So far, the field of chemosensory neuroimaging is dominated by studies that examine the role of brain regions in isolation. However, to completely understand neural processing of chemosensation, we must also examine interactions between regions. In general, the use of connectivity methods has increased in the neuroimaging field, providing important insights to physical sensory processing, such as vision, audition, and touch. A similar trend has been observed in chemosensory neuroimaging, however, these established techniques have largely not been rigorously applied to imaging studies on the chemical senses, leaving network insights overlooked. In this article, we first highlight some recent work in chemosensory connectomics and we summarize different connectomics techniques. Then, we outline specific challenges for chemosensory connectome neuroimaging studies. Finally, we review best practices from the general connectomics and neuroimaging fields. We recommend future studies to develop or use the following methods we perceive as key to improve chemosensory connectomics: 1) optimized study designs, 2) reporting guidelines, 3) consensus on brain parcellations, 4) consortium research, and 5) data sharing.